The Effect of Spironolactone on β-amyloid-Induced Memory Impairment in Male Rats: The Role of Microglial Inhibition - Mohammad Mehdipour; Masoumeh Emamghoreishi; Majid Reza Farrokhi; Elahe Amirinezhadfard; Mojtaba Keshavarz (Tabriz University of Medical Sciences, 2022)
Purpose: Neuroinflammation was indicated in the pathophysiology of Alzheimer's disease(AD). Previous reports have also signified that spironolactone has anti-inflammatory effects.Therefore, the aim of this study was to assess the modulatory effects of spironolactone onneuroinflammation and memory loss in a rat model of AD.Methods: The β-amyloid protein fragment 25-35 (Aβ) was injected in the dorsal hippocampus (5μg/2.5 μL each side) of male Sprague-Dawley rats for four consecutive days to induce memoryimpairment. Animals have intraperitoneally received spironolactone (10, 25, or 50 mg/kg, N = 6/group) or vehicle for 14 days. The passive inhibitory avoidance and the novel recognition testswere used for memory evaluation. Neuroinflammation was assessed by measuring the level ofIba1 protein, a marker of microglial activation, using western immunoblotting.Results: Different doses of spironolactone showed no significant changes in latency times anddiscriminations ratios in passive inhibitory avoidance and novel recognition tests, respectively,as compared to vehicle. However, spironolactone-treated groups showed significantly lowerIba1 protein levels in comparison to the vehicle-treated group (P < 0.01).Conclusion: Spironolactone had a modulatory effect on neuroinflammation through a repressiveeffect on microglial activation with no valuable effect on memory improvement in a rat modelof AD. The findings of this study suggest that Aβ-induced memory loss may not be directly linkedto microglial activation. Spironolactone may be a potential candidate to be examined in otherneuroinflammatory disorders.